Mechanical impulse enhancement in MEMS using porous silicon combustion process - A. V. Dolbik; A. Yu. Zubov; S. N. Krisevich; A. S. Sychevich; A. V. Korotkevich; S. K. Lazarouk; V. A. Labunov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Nanostructured porous silicon impregnated by solid state oxidants has been studied in order to provide the mechanical impulse for jet-propulsion microsystems. The system with jet-propulsion movement on a silicon chip has been used for impulse measurements. The estimated impulse value is in the range of 25-130 mN·s by using of carrying platform for Si chips.